Health services utilisation disparities between English speaking and non-English speaking background Australian infants - Chen Jack; Ou Lixin; Hillman Ken (BMC, 2010)
Abstract Background To examine the differences in health services utilisation and the associated risk factors between infants from non-English speaking background (NESB) and English speaking background (ESB) within Australia. Methods We analysed data from a national representative longitudinal study, the Longitudinal Study of Australian Children (LSAC) which started in 2004. We used survey logistic regression coupled with survey multiple linear regression to examine the factors associated with health services utilisation. Results Similar health status was observed between the two groups. In comparison to ESB infants, NESB infants were significantly less likely to use the following health services: maternal and child health centres or help lines (odds ratio [OR] 0.56; 95% confidence intervals [CI], 0.40-0.79); maternal and child health nurse visits (OR 0.68; 95% CI, 0.49-0.95); general practitioners (GPs) (OR 0.58; 95% CI, 0.40-0.83); and hospital outpatient clinics (OR 0.54; 95% CI, 0.31-0.93). Multivariate analysis results showed that the disparities could not be fully explained by the socioeconomic status and language barriers. The association between English proficiency and the service utilised was absent once the NESB was taken into account. Maternal characteristics, family size and income, private health insurance and region of residence were the key factors associated with health services utilisation. Conclusions NESB infants accessed significantly less of the four most frequently used health services compared with ESB infants. Maternal characteristics and family socioeconomic status were linked to health services utilisation. The gaps in health services utilisation between NESB and ESB infants with regard to the use of maternal and child health centres or phone help, maternal and child health nurse visits, GPs and paediatricians require appropriate policy attentions and interventions.